Effect of Some Modified Hochland Solutions and Nacl on the Growth of Phaseolus Aureus L - Hassan, Fatima Ali Howaidy; Madloul, Jinan Riyad Kadhum; Hassoon, Dhuha Saleem Abdulrasool; Shokry, Luma Zuhair Salih (American Journal of Biomedicine and Pharmacy, 2024)
The effect of complete and modified Hochland solutions (nitrogen deficient solution, phosphorus deficient solution, iron deficient solution, micronutrient deficient solution) in addition to sodium chloride solution at a concentration of 200 mmol/L on the growth of mung bean plant for 30 days in the advanced plant laboratory was studied. After the experiment was completed, mung bean plant was harvested and the plant physiological indicators were estimated, represented by plant height, fresh and dry weights, and chlorophyll a and b content and total. We note that the plants grown in the Hochland solution deficient in nitrogen as well as the sodium chloride solution recorded the highest plant height and fresh and dry weights in the plants treated with complete Hochland solution compared to the control (distilled water) and tap water, while the rest of the treatments recorded the lowest rate of physiological indicators when treated with sodium chloride solution, and the other treatments had an effect between them.